Robbers and Soldiers: Criminality and Roman Army in Apuleius’ Metamorphoses - Garraffoni, Renata (Gerión. Revista de Historia Antigua, 2005)
This paper aims at discussing the relationship between ancient robbers and Roman army in Apuleius’ Metamorphoses. As Apuleius’ Metamorphoses has a great deal of information about banditry, deserters and ex-soldiers that can be explored in different ways, I suggest that this ancient author can provide us the possibility to rethink some historiographical approaches used to study the Roman plebs.